Democracy and leadership on pragmatism and virtue - Weber, Eric Thomas (Lexington Books, 2013)
In Democracy and Leadership, Weber draws from Plato's virtues of the ideal city, updated with democratic values and insights from John Dewey, to present both a general and a democratic theory of leadership. Central to the project is the democratic turn away from thinking of leadership as persons to thinking of it as a process open to all